New materials for adsorption heat transformation and storage. (September 2017) - Henninger, Stefan K.; Ernst, Sebastian-Johannes; Gordeeva, Larisa; Bendix, Phillip; Fröhlich, Dominik; Grekova, Alexandra D.; Bonaccorsi, Lucio; Aristov, Yuri; Jaenchen, Jochen
Abstract: Great current progress in the materials science offers an enormous choice of novel adsorbents which may be promising for transformation and storage of low temperature heat, e.g. from renewable heat sources. This paper gives an overview of recent trends and achievements in this field. We consider possible optimization of zeolites by dealumination, further development on aluminophosphates, composites "salt in porous host matrice" and metal-organic frameworks which are currently receiving the largest share of scientific attention. The particular attention is focused on the chemical nano-tailoring and tunable adsorption behavior of these materials to satisfy the demands of appropriate heat transformation cycles. We hope that this review will give new impact on target-oriented research on the novel adsorbents for heat transformation and storage. Highlights: Optimized zeolites by dealumination. Functionalization of aluminophosphates. MOFs MIL-100, CAU-10 and HKUST-1 for the use in heat pumps. Composites based on LiCl and Multiwall Carbon Nano-Tubes. Direct crystallization of HKUST-1 on full scale heat exchanger (see picture).